The Plant Growth Analysis of Cucumis sativus L. Affected by Various Types of Organic Matter - Nasrudin Nasrudin; Jihad Muhammad; R. Arif Malik Ramadhan (JERAMI : Indonesian Journal of Crop Science, 2023)
Organic matter can be used to increase the growth and metabolism activities of Cucumis sativus L. plants. Plant growth analysis is a simple method that can be used to determine physiological activities that support plant growth. The study aims to describe plant activities through plant growth analysis which is influenced by the use of organic matter. The research was conducted at the Experimental Garden, Faculty of Agriculture, Universitas Perjuangan Tasikmalaya. The study used a Completely Randomized Design - single factor (types of organic matters) i.e. control, rice straw compost, rice husk, leaf green compost, and cow manure. Four replications were used in this study. Based on our study, the application of organic matter significantly affects LAI 2 WAP, LAI 4 WAP, WC 2 WAP, WC 4 WAP, NAR, PGR, and HI. Cow manure, green leaf compost, and rice straw compost can increase LAI, while rice husk, rice straw, and green cow manure can increase WC. Furthermore, the application of rice husk and cow manure was able to increase in NAR, CGR, and HI. The increase NAR, CGR, and HI in this study was positively correlated with r= 0.622 and r= 0.284, respectively.